PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF GROUP RESUME TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN FIKIH DI MADRASAH ALIYAH AL- KHAIRAT PANGKALAN LESUNG KABUPATEN PELALAWAN - Yulianti, Ilpira; Afriani, Gusma; Hendri, Muspika (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
This research was instigated with the low of student comprehension about learning material.  This research aimed at finding out the effect of implementing Group Resume active learning strategy toward student comprehension on Fikih subject at Islamic Senior High School of Al-Khairat Pangkalan Lesung, Pelalawan Regency.  It was quantitative research with pre-experiment and one group pretest-posttest design.  All the eleventh-grade students learning on Fikih subject at Islamic Senior High School of Al-Khairat Pangkalan Lesung, Pelalawan Regency were the population of this research, and they were 15 students.  Total sampling technique was used in this research.  15 the eleventh-grade students of Social Science were the samples.  Observation, test, and documentation were the techniques of collecting data.  Paired sample t-test was the technique of analyzing data.  Based on the data analysis results, there was an effect of implementing Group Resume active learning strategy toward student comprehension on Fikih subject at Islamic Senior High School of Al-Khairat Pangkalan Lesung, Pelalawan Regency.  It was proven with the calculation score of sig (2 tailed) lower than α (0.000<0.05).  The result of posttest mean 76.67 was higher than the pretest 52.33.